Peran Persepsi Risiko dan Persepsi Nilai Pada Niat pembelian Makanan Berbasis nabati Oleh Konsumen Vegetarian - Elbi Elisius Brahmana; Hommy Dorthy Ellyany Sinaga (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The growth of plant-based food consumption is increasing along with the increasing awareness of health, environmental desires, and animal ethics, especially among vegetarian consumers. This study aims to analyze the role of perceived risk and perceived value in influencing plant-based food purchase intention. Perceived risk includes consumer concerns about the health, financial, and social aspects of the product, while perceived value includes the functional, emotional, and ethical benefits perceived from consuming plant-based products. This study uses a qualitative research approach and library research which is useful for obtaining a series of descriptions of the factors that influence the results of the variables studied. This research step uses a data collection method from online journal literature sourced from Google Scholar..